Assessment of ESL Sociopragmatics for Informing Instruction in an Academic Context: From Australia to Canada - Kolesova, Valeriia (Université d'Ottawa / University of Ottawa, 2016)
This mixed methods study aimed to provide some validity evidence for the use of the ESL sociopragmatics test developed by Roever, Elder and Fraser (2014) for formative purposes. The test developers recommend further validation of the tool, originally developed for the Australian context. In this study, the test items were used to reveal areas of weakness in sociopragmatic knowledge in a group of learners of an academically oriented English Intensive Program in Canada. Analysis of the test scores revealed a lack of knowledge of norms of appropriateness and politeness in English, which was further targeted with an instructional unit informed by the items of the test. Two weeks after the instructional unit was delivered, the participants were asked to complete a follow-up questionnaire. The questionnaire results provided insight into the participants’ perceptions of usefulness of the instructional unit. The learners found explicit instruction on ESL sociopragmatics useful for their language learning experience as well as day-to-day interactions in English. Particularly, they claimed to feel more confident communicating in English after receiving explicit instruction on ESL sociopragmatics. They were able to use information from the lesson in situations such as talking to their language instructors, communicating with university personnel, and participating in service encounter interactions. Therefore, the test proved to have potential for developing instructional materials in an academic context. Based on the findings of the study, suggestions on incorporating sociopragmatic competence into the institution’s EAP curriculum were made.
Keywords: ESL; EFL; Bilingualism; Assessment; Linguistics; Sociopragmatics; Appropriateness; Pragmatics; EAP